Organizaciones Virtuales (2019)
Virtual Organizations are new organizational forms originated from both the replacement of face to face communications by remote communications supported by electronic means, and from the accesibility of real time information about the operation of the company, for all employees. This article pursues the following goals: 1) To define virtual organization, review its sociotechnical antecedents and propose a preliminary classification into inter-organizational and intra-organizational forms. 2) To discuss the characteristics of virtual organizations and their impact on organizational design, and 3) To compare virtual organizations toother organizational forms.